2021
DOI: 10.3390/ijms22126262
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Reprogramming of Colorectal Cancer Cells and the Microenvironment: Implication for Therapy

Abstract: Colorectal carcinoma (CRC) is one of the most frequently diagnosed carcinomas and one of the leading causes of cancer-related death worldwide. Metabolic reprogramming, a hallmark of cancer, is closely related to the initiation and progression of carcinomas, including CRC. Accumulating evidence shows that activation of oncogenic pathways and loss of tumor suppressor genes regulate the metabolic reprogramming that is mainly involved in glycolysis, glutaminolysis, one-carbon metabolism and lipid metabolism. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 330 publications
1
57
0
Order By: Relevance
“…By detecting markers of epithelial cells and mesenchymal cells, the blocked EMT process could partially explain decreased migration abilities in 786-O cells after LINC00342 knockdown. Aberrant glycolytic level of tumor cells could affect the interaction of cancer cells with the TME, leading to immune resistance or even escaping immune surveillance (25,26). Recent studies have shown that lncRNAs play crucial roles in regulating immunity (27), which may be partly explained by the lncRNA interfering glycolysis process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By detecting markers of epithelial cells and mesenchymal cells, the blocked EMT process could partially explain decreased migration abilities in 786-O cells after LINC00342 knockdown. Aberrant glycolytic level of tumor cells could affect the interaction of cancer cells with the TME, leading to immune resistance or even escaping immune surveillance (25,26). Recent studies have shown that lncRNAs play crucial roles in regulating immunity (27), which may be partly explained by the lncRNA interfering glycolysis process.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant glycolytic level of tumor cells could affect the interaction of cancer cells with the TME, leading to immune resistance or even escaping immune surveillance ( 25 , 26 ). Recent studies have shown that lncRNAs play crucial roles in regulating immunity ( 27 ), which may be partly explained by the lncRNA interfering glycolysis process.…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypically, this is evidenced by an shifts in total lipid content in tumor compared to healthy tissues, altered triacylglycerol and cholesterol storage in lipid droplets (LDs) [ 31 , 32 ] and differential expression of genes encoding for lipogenic related enzymes [ 33 ] (affected pathways summarized in Figure 1 ). As a consequence, abnormal lipid metabolism of CRC cells affects numerous processes such as apoptosis, autophagy, necrosis, proliferation, differentiation, growth, plasticity and thereby drives tumor initiation and progression which are significant for the advancement and poor prognosis of CRC [ 12 , 30 , 34 , 35 , 36 ].…”
Section: Lipid Biology In Crcmentioning
confidence: 99%
“…Membrane-associated proteins that have been described to mediate fatty acid uptake include fatty acid transport proteins (FATP), fatty acid binding proteins (FABP) and the best characterized scavenger receptor, CD36, also known as fatty acid translocase (FAT). A body of knowledge and evidence has been collected for CD36, indicating a critical role in many entities, as CRC, gastric, cervical or ovarian cancer, impacting an array of signaling pathways, but the overall conclusion concerning the role of CD36 remains inconsistent [ 36 ]. Upregulation on cancer cells was associated with poor prognosis, increased storage of FAs in LDs and activation resulted in proliferation inhibition and induced apoptosis in CRC [ 50 , 51 ].…”
Section: Lipid Biology In Crcmentioning
confidence: 99%
“…At present, TME plays an essential role in CRC and gradually gains prominence as a new therapeutic target for the reversal of resistance (12,13). Advances in the understanding of the TME have contributed to the exploration of treatments for advanced CRC (14).…”
Section: Introductionmentioning
confidence: 99%